Development of Flood Disaster Management Module as a Means of Elementary School Learning Enrichment - Kiki Aryaningrum; Arief Kuswidyanarko; Ali Fakhrudin; Aldora Pratama; Husnil Kirom; Siti Rachmi Indah Sari; Ahmad Adi Suhendra (International Conference on Elementary Education, 2023)
This study aims to develop a flood disaster management module as a means of enriching elementary school learning. This development research aims to develop a flood disaster management module and the feasibility of the flood disaster management module media as a means of enriching elementary school learning. The method in this study was carried out using the Borg and Gall Research & Development model which has been modified by Sugiyono covering 7 stages, namely: 1) potentials and problems, 2) collecting data, 3) product design, 4) design validation, 5) design revision, 6) product trials, 7) product revisions. The results of this study indicate that the results obtained from the validation of material experts obtained an average of 81% with the "Easy" criteria. validation of linguists in the flood disaster management module obtained an average percentage of 85% with very decent criteria. The average percentage of student responses to the flood disaster management module is positive. Students respond that the module is easy to understand, gives a feeling of pleasure, is presented in an orderly and systematic manner, illustrations support imagination, and can increase knowledge about flood prevention. This shows that the flood disaster management module as a means of enriching elementary school learning produced in this study is considered appropriate for use as learning enrichment material in elementary schools